In-situ fluorinated lithium-aluminum layered double-metal hydroxide as well as preparation method and application thereof
By mixing the strong acid salt of lithium fluoride and aluminum with alkaline reagents, the efficient preparation of in-situ fluorinated lithium aluminum layered bimetallic hydroxide is achieved, and the inefficient preparation process and high cost in the prior art are solved. The problem of this achieves efficient utilization of lithium and fluorine elements.
Patent Information
- Application Number
- CN202411468122.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, the preparation process of fluorinated lithium-aluminum layered bimetallic hydroxide is inefficient and time-consuming and has high production costs.
The preparation of in-situ fluorinated lithium aluminum layered bimetal hydroxide is achieved by mixing the strong acid salt of lithium fluoride and aluminum to form a dissolved mixed solution and mixing it with alkaline reagents. This method simplifies the process, improves the utilization rate of lithium and fluorine, and reduces production costs.
It realizes efficient preparation of lithium-aluminum layered bimetallic hydroxide, reduces production costs, avoids additional fluorination steps and waste of water resources, and is simple and efficient in process and convenient in operation.
Smart Images

Figure CN119409217A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to an in-situ fluorinated lithium aluminum layered double metal hydroxide and a preparation method and application thereof. Background Art
[0002] Layered double hydroxides (LDHs) are formed by the combination and orderly stacking of positively charged two-dimensional metal hydroxide plates and interlayer anions. LDHs materials have good chemical stability, high specific surface area and excellent ion exchange capacity, so they are widely used in adsorbents, ion extractants, catalysts, flame retardants, energy conversion and storage, metal anti-corrosion coatings and even biomedicine.
[0003] The structure of LDHs is mostly formed by partial replacement of some metal cations in divalent metal cation hydroxides by trivalent metal cations. In 1977, Serna et al. firstly used monovalent metal cation Li + LiAlLDH was prepared by inserting Al(OH)3, where Li + Occupies the octahedral vacancies of the Al(OH)3 structure to form positively charged layers and the charges are balanced by interlayer anions. [LiAl2(OH)6] + (A n– 1 / n )·mH2O (denoted as LiAl-ALDH, A is the interlayer anion) is the only M + -M 3+ LDHs.
[0004] The article "Chemical Engineering Journal" published in Issue 395 of 2020 puts Al(OH)3 and 10MLiCl solution (feeding molar ratio is Li:Al=3.9:1) into an autoclave, and hydrothermally heats at 90°C for 24 hours to obtain LiAlLDHs product (Chem.Eng.J., 2020, 395125187). Chinese patent document CN 107500321 A discloses a method for preparing LiAl LDHs by nitrate intercalation, which is prepared by adding lithium nitrate, aluminum nitrate, and a precipitant to water, dissolving and obtaining a reaction mixture; reacting the reaction mixture in a hydrothermal autoclave at 120-160°C for 24-48 hours; separating, washing and drying the precipitate after the reaction to obtain a nitrate intercalated lithium aluminum layered double metal hydroxide. The preparation method of LiAl LDH disclosed in the above prior art has the defects of being inefficient, time-consuming, or having high production costs.
[0005] In addition, fluorinated nano-inorganic materials have important application prospects in the fields of energy storage batteries and lithium extraction from salt lakes. However, both lithium fluoride and aluminum fluoride are not easily soluble in common solvents such as water, so the reaction process is slow and inefficient. The conventional method adopts a two-step process scheme, namely, first synthesizing non-fluorinated LiAl LDH, and then preparing fluorinated lithium aluminum layered double hydroxide through ion exchange substitution with dissolved fluoride-containing salts. The process is complicated and consumes a lot of water resources. Summary of the invention
[0006] The technical problem solved by the present invention is to overcome the defects of the prior art in the preparation process of fluorinated lithium aluminum layered double metal hydroxide, which is inefficient, time-consuming and has high production cost, and to provide an in-situ fluorinated lithium aluminum layered double metal hydroxide and a preparation method and application. The preparation method of the present invention has a simple and efficient process, is easy to operate, and effectively improves the utilization rate of lithium and fluorine elements, greatly reduces production costs, and is economical and environmentally friendly.
[0007] The invention mixes lithium fluoride and a strong acid salt of aluminum. Since lithium fluoride is more difficult to dissolve than aluminum fluoride, a mixed solution containing lithium fluoride and a strong acid salt of aluminum can be obtained, which greatly improves the dynamics of lithium ion embedding into the Al(OH)3 structure in the subsequent reaction. Then, the mixed solution containing lithium fluoride and a strong acid salt of aluminum is mixed with an alkaline reagent, thereby realizing the controllable preparation of in-situ fluorinated lithium aluminum layered double metal hydroxide. In the reaction process, octahedral vacancies are formed under the action of the alkaline reagent and are occupied by Li + The occupied Al(OH)3 plate structure, while F - The in-situ intercalation doping can be achieved by entering the interlayer, which greatly improves the fluorination efficiency and avoids the waste of reagents and water resources caused by the additional fluorination step, as well as the complexity of the process. Furthermore, when the OH provided by the alkaline reagent in the reaction system - When the theoretical amount of LiAl LDH is exceeded and / or non-lithium fluoride lithium salt is added, the excess OH - The additional addition of non-fluorinated lithium salt can effectively regulate the nucleation and growth process of fluorinated LiAl LDH through the chemical potential effect, inhibiting the generation of by-products. The entire preparation method is simple, efficient, and easy to operate. At the same time, it effectively improves the utilization rate of lithium and fluorine elements, greatly reduces costs, and is economical and environmentally friendly.
[0008] The present invention solves the above technical problems through the following technical solutions:
[0009] The present invention provides a method for preparing an in-situ fluorinated lithium aluminum layered double metal hydroxide, which comprises the following steps:
[0010] The "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is mixed with an alkaline reagent to form a suspension through reaction, and then solid-liquid separation is performed to obtain the in-situ fluorinated lithium aluminum layered double metal hydroxide;
[0011] The molar ratio of the lithium fluoride to the aluminum element in the strong acid salt of aluminum is 1:2; the OH provided by the alkaline reagent in the reaction system - The molar ratio of the aluminum element to the aluminum strong acid salt is not less than 3:1.
[0012] In the present invention, the strong acid salt of aluminum may be one or more of aluminum nitrate, aluminum sulfate and aluminum chloride.
[0013] In the present invention, the preparation method of the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" can be conventional in the art, for example, lithium fluoride and a strong acid salt of aluminum are added to a solvent and dissolved to obtain the solution, or lithium fluoride is added to a solution containing a strong acid salt of aluminum and dissolved to obtain the solution.
[0014] In the present invention, the solvent in the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is generally deionized water and / or an alcohol solvent. The alcohol solvent is preferably one or more of methanol, ethanol, n-propanol, isopropanol, propylene glycol, glycerol and tert-butyl alcohol.
[0015] In the present invention, in the "mixed solution containing lithium fluoride and a strong acid salt of aluminum", the concentration of the strong acid salt of aluminum can be conventional in the art, generally not exceeding the concentration corresponding to its maximum solubility at the temperature in the solvent (e.g., deionized water), preferably 0.5-6 mol / L, such as 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L. From the perspective of cost saving, ease of operation and controllability, the temperature is generally an ambient temperature of 15-35°C.
[0016] In the present invention, the alkaline reagent can be a conventional alkaline reagent in the art that can provide OH by ionization and / or hydrolysis in the reaction system. - The substance is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia monohydrate, sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate, more preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide and ammonia monohydrate.
[0017] In the present invention, the OH provided by the alkaline reagent in the reaction system - The molar ratio of the aluminum element in the strong acid salt of aluminum is preferably greater than 3:1, more preferably (3-18):1 but not including 3:1, and further preferably (3-12):1 but not including 3:1, for example 4.5:1.- When the molar ratio of the aluminum element in the strong acid salt of aluminum is greater than 3:1, the additional OH - The nucleation and growth process of fluorinated LiAl LDH can be effectively regulated by the chemical potential effect, thereby inhibiting the formation of by-products.
[0018] When the alkaline reagent provides OH by ionization in the reaction system - When the substance is (such as sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonia monohydrate), the OH in the alkaline reagent is - The molar ratio of the aluminum element in the strong acid salt of aluminum is preferably greater than 3:1, more preferably (3-18):1 and excluding 3:1, and further preferably (3-12):1 and excluding 3:1, for example 4.5:1.
[0019] In the present invention, the alkaline reagent is preferably mixed with the "mixed solution of a strong acid salt containing lithium fluoride and aluminum" in the form of an alkaline reagent solution. The concentration of the alkaline reagent solution may be conventional in the art, generally not exceeding the concentration corresponding to its maximum solubility at the temperature in the solvent (e.g., deionized water), preferably 0.5-10 mol / L, such as 6 mol / L, 8 mol / L or 9 mol / L. From the perspective of cost saving, ease of operation and controllability, the temperature is generally an ambient temperature of 15-35°C. The solvent in the alkaline reagent solution is generally deionized water and / or an alcohol solvent. The alcohol solvent is preferably one or more of methanol, ethanol, n-propanol, isopropanol, propylene glycol, glycerol and tert-butanol.
[0020] In the present invention, preferably, the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is added to the alkaline reagent. When the alkaline reagent is in the form of an alkaline reagent solution, preferably, the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is added to the alkaline reagent solution.
[0021] In the present invention, in order to further improve the purity of the in-situ fluorinated lithium aluminum layered double hydroxide, preferably, a non-fluorinated lithium salt is added before the reaction. The non-fluorinated lithium salt can effectively regulate the nucleation growth process of the fluorinated LiAl LDH through the chemical potential effect, thereby inhibiting the generation of by-products.
[0022] The timing of adding the non-lithium fluoride lithium salt can be conventional in the art, for example, adding it to the "mixed solution of the strong acid salt containing lithium fluoride and aluminum", or first mixing it with the alkaline reagent, or adding it to the reaction system after the "mixed solution of the strong acid salt containing lithium fluoride and aluminum" and the alkaline reagent are mixed.
[0023] Wherein, the non-lithium fluoride lithium salt can be a conventional lithium salt in the art that can be completely dissolved in the reaction system after the "mixed solution containing lithium fluoride and aluminum strong acid salt" and the alkaline reagent are mixed, preferably one or more of lithium nitrate, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium acetate, lithium difluorooxalate borate, lithium bisoxalate borate, lithium bisfluorosulfonyl imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium sulfonate. The lithium sulfonate is preferably a lithium salt of an organic acid containing a sulfonic acid group, for example, one or more of lithium 4-methylbenzenesulfonate, lithium trifluoromethylsulfonate, and lithium methanesulfonate.
[0024] The molar ratio of lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is preferably (0.1-2):1, more preferably (0.1-1):1, for example 0.5:1.
[0025] In some preferred embodiments, when the OH provided by the alkaline reagent in the reaction system - When the molar ratio of the aluminum element in the strong acid salt of aluminum is 3:1, the molar ratio of the lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is (0.1-2):1.
[0026] In some preferred embodiments, when the OH provided by the alkaline reagent in the reaction system - When the molar ratio of the aluminum element in the strong acid salt of aluminum is greater than 3:1, the molar ratio of the lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is (0.1-2):1.
[0027] In the present invention, the reaction is generally carried out under stirring. The stirring speed may be 200-800 rpm, for example 500 rpm.
[0028] In the present invention, the reaction can be carried out under normal pressure or under pressure. The reaction temperature can be 5-200° C., preferably 10-100° C., more preferably 25-95° C., such as 90° C. The reaction time can be 0.5-96 h, preferably 3-72 h, more preferably 3-48 h, such as 6 h, 10 h or 24 h.
[0029] In the present invention, the solid-liquid separation may be carried out in a conventional manner in the art, such as filtration, centrifugation or decantation. According to conventional methods in the art, washing and drying are generally required after the solid-liquid separation.
[0030] The present invention also provides an in-situ fluorinated lithium aluminum layered double metal hydroxide prepared by the above-mentioned preparation method.
[0031] In the present invention, the chemical formula of the in-situ fluorinated lithium aluminum layered double metal hydroxide can be nLi(F x ,A (1-x) / y)·2Al(OH)3·mH2O, where A is NO3 - 、SO4 2- 、CO3 2- OH - , Cl - Br - and I - One or more of , 0<n≤1, 0<m≤6, 0<x≤1, y is the valence number of element A.
[0032] In the present invention, the interlayer anions of the in-situ fluorinated lithium aluminum layered double metal hydroxide are in addition to F - It may also include anions. When the anions include NO3 - 、SO4 2- , Cl - Br - and I - When one or more of the anions are present, the anions may be derived from the strong acid salt of aluminum and / or the non-fluorinated lithium salt; when the anions include CO3 2- When CO3 2- It can be derived from CO2 in the air entering the reaction system; when the anion includes OH - When, OH - The LiAl LDH interlayer can be introduced by an excess of alkaline reagent.
[0033] The present invention also provides an application of the in-situ fluorinated lithium aluminum layered double metal hydroxide in a lithium secondary battery separator coating.
[0034] In the present invention, in the lithium secondary battery separator coating, the mass percentage of the in-situ fluorinated lithium aluminum layered double metal hydroxide may be 10%-30%, for example, 23.3%.
[0035] In the present invention, the lithium secondary battery separator coating preferably further comprises a dispersant, a binder and a dispersion medium.
[0036] The dispersant may be conventional in the art, such as one or more of sodium hexametaphosphate, ammonium polyacrylate, sodium polyacrylate, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyethylene glycol and polyvinyl pyrrolidone, for example, sodium hexametaphosphate.
[0037] Wherein, in the lithium secondary battery separator coating, the mass percentage of the dispersant may be 0.1%-0.5%, for example 0.23%.
[0038] The binder may be conventional in the art, such as one or more of polyvinyl alcohol, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polymethyl acrylate, polymethacrylic acid and polyethylene oxide, such as polyvinyl alcohol and polyacrylic acid.
[0039] Wherein, in the lithium secondary battery separator coating, the mass percentage of the binder may be 1%-5%, for example, 1.9%.
[0040] Wherein, the dispersion medium is generally deionized water.
[0041] Wherein, in the lithium secondary battery separator coating, the mass percentage of the dispersion medium may be 50%-85%, for example, 74.5%.
[0042] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0043] The reagents and raw materials used in the present invention are commercially available.
[0044] The positive and progressive effects of the present invention are:
[0045] (1) The preparation method of the present invention is simple and efficient, and effectively improves the utilization rate of lithium and fluorine elements, greatly reduces the production cost, and is economical and environmentally friendly;
[0046] (2) The preparation method of the present invention avoids the waste of reagents and water resources and the complication of the process caused by pre-synthesizing lithium aluminum layered double metal hydroxide and then fluorinating it;
[0047] (3) The preparation method of the present invention does not require a high temperature and high pressure hydrothermal reaction process. The crystallinity, morphology and doping content of the fluorine element intercalation of the lithium aluminum layered double hydroxide can be regulated by the amount of the alkaline reagent, and further, can also be regulated by adding non-fluorinated lithium salts, which is easy to operate.
[0048] (4) In the conventional LiAl LDH synthesis method, a large excess of Li is often required. + Source and OH - The input of F source often results in waste of expensive Li source, and the collection or neutralization of excess alkali also results in high synthesis cost. However, in the preparation method of the present invention, no additional F is needed. - The LDH is synthesized in situ to obtain a lithium aluminum layered double hydroxide with a high fluorine intercalation doping amount, thereby avoiding an additional fluorination step. In addition, the product synthesized by the present invention has a large solid content before solid-liquid separation, thereby effectively avoiding the waste of water resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a SEM image of the product prepared in Example 1 of the present invention.
[0050] Figure 2 This is the XRD pattern of the product prepared in Example 1 of the present invention.
[0051] Figure 3 This is a SEM image of the product prepared in Example 2 of the present invention.
[0052] Figure 4 This is the XRD pattern of the product prepared in Example 2 of the present invention.
[0053] Figure 5 This is a SEM image of the product prepared in Example 3 of the present invention.
[0054] Figure 6 This is the XRD pattern of the product prepared in Example 3 of the present invention.
[0055] Figure 7 This is a SEM image of the product prepared in Example 4 of the present invention.
[0056] Figure 8 This is the XRD pattern of the product prepared in Example 4 of the present invention.
[0057] Fig. 9 This is a SEM image of the product prepared in Example 5 of the present invention.
[0058] Fig.10 This is the XRD pattern of the product prepared in Example 5 of the present invention.
[0059] Fig.11 This is a SEM image of the product prepared in Example 6 of the present invention.
[0060] Fig.12 This is the XRD pattern of the product prepared in Example 6 of the present invention.
[0061] Fig.13 This is a SEM picture of the product prepared in Comparative Example 1 of the present invention.
[0062] Fig.14 This is the XRD diagram of the product prepared in Comparative Example 1 of the present invention.
[0063] Fig.15 This is a SEM picture of the product prepared in Comparative Example 2 of the present invention.
[0064] Fig.16 This is the XRD diagram of the product prepared in Comparative Example 2 of the present invention.
[0065] Fig.17 This is a SEM picture of the product prepared in Comparative Example 3 of the present invention.
[0066] Fig.18 This is the XRD diagram of the product prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0067] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0068] Example 1
[0069] LiF and Al(NO3)3·9H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and Al(NO3)3 are 1 mol / L and 2 mol / L, respectively; KOH powder is added into deionized water and dissolved to form a 6 mol / L KOH solution; the mixed solution of LiF and Al(NO3)3 is added into an equal volume of KOH solution, and reacted at 90°C and 500 rpm for 6 hours under normal pressure to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0070] Figure 1 The SEM image of Example 1 is shown, showing the typical flake morphology of the LDH product. Figure 2 The XRD pattern of the product prepared in Example 1 shows that the diffraction peaks mainly correspond to the highly crystalline lithium aluminum layered double hydroxide LiAl-NO3, FLDH, accompanied by a weaker Al(OH)3 peak. + :Al 3+ :OH - :F - The ratio of Li is 1:2:6:1, and the feed is completely in accordance with the stoichiometric ratio, and only a small amount of Li + Al(OH)3 structure is not inserted, compared with the large excess of Li salt and OH required in the conventional LiAl LDH synthesis process - The addition of shows that the preparation method of the in-situ fluorine intercalated lithium aluminum layered double metal hydroxide of the present invention has excellent reaction kinetics.
[0071] Example 2
[0072] LiF and Al(NO3)3·9H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and Al(NO3)3 are 1 mol / L and 2 mol / L, respectively; KOH and LiNO3 powders are added to deionized water and dissolved to form a mixed solution of 9 mol / LKOH and 0.5 mol / L LiNO3; the mixed solution of LiF and Al(NO3)3 is added to an equal volume of a mixed solution of KOH and LiNO3, and the mixture is reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0073] Figure 3 The SEM image shows that the LDH material synthesized in Example 2 has a columnar particle morphology formed by stacking and growing a lamellar structure; Figure 4 The XRD diagram of the product of Example 2 shows the synthesis of pure LiAl-NO3, F LDH. Compared with Example 1, the KOH added in Example 2 provides 50% excess OH - Add 50% excess Li + Source, and Al 3+ and F - The input amount remains unchanged, which indicates that the synthesis of LDH + The reaction kinetics of Al(OH)3 insertion can be effectively controlled by a combination of the amount of alkaline reagent used and the addition of non-fluorinated lithium salts.
[0074] Example 3
[0075] LiF and Al(NO3)3·9H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and Al(NO3)3 are 1 mol / L and 2 mol / L, respectively; KOH and LiNO3 powders are added to deionized water and dissolved to form a mixed solution of 6 mol / LKOH and 0.5 mol / L LiNO3; the mixed solution of LiF and Al(NO3)3 is added to an equal volume of a mixed solution of KOH and LiNO3, and the mixture is reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0076] Figure 5 The SEM images show that the LDH synthesized in Example 2 is a uniform and independent flake morphology; Figure 6 The XRD diagram of the product of Example 2 shows the synthesis of pure LiAl-NO3, F LDH. Compared with Example 1, the raw material composition of Example 3 contains 50% excess Li +Source, and Al 3+ OH - and F - The input amount remains unchanged, which indicates that the synthesis of LDH + The reaction kinetics of Al(OH)3 insertion can be effectively regulated by adding non-fluorinated lithium salts. - The amount of intercalation can also be effectively controlled over a wide range (until close to the theoretical doping ratio, see Table 1) by combining the amount of alkaline reagent used and the addition of non-lithium fluoride lithium salt.
[0077] Example 4
[0078] LiF and Al(NO3)3·9H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and Al(NO3)3 are 1 mol / L and 2 mol / L, respectively; KOH powder is added into deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of LiF and Al(NO3)3 is added into an equal volume of KOH solution, and reacted at 90°C and 500 rpm for 6 hours under normal pressure to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0079] The SEM image shows that the product has a stacked growth layer structure ( Figure 7 );Depend on Figure 8 It can be seen that compared with Example 1, Example 4 obtained a pure LiAl-NO3, F LDH product. Compared with Example 1, the KOH added in Example 4 provided 50% excess OH - , and Al 3+ , Li + and F - The input amount remains unchanged, which indicates that the synthesis of LDH + The reaction kinetics of Al(OH)3 insertion can be effectively regulated by the amount of alkaline reagent used.
[0080] Example 5
[0081] LiF and Al2(SO4)3·18H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and Al2(SO4)3 are both 1 mol / L; KOH powder is added into deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of LiF and Al2(SO4)3 is added into an equal volume of KOH solution, and reacted at 90°C and 500 rpm for 6 hours under normal pressure to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0082] Fig. 9 and Fig.10 The SEM and XRD test results of the product obtained in Example 4 are shown respectively. It can be seen that similar to Example 2, when the input amounts of other elements are consistent with the theoretical stoichiometric ratio of the product composition, only OH - When the source is in excess of 50%, pure LiAl-SO4, F LDH can be obtained. The product has a clear morphology of nanosheet stacking and bridging.
[0083] Example 6
[0084] LiF and AlCl3·6H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiF and AlCl3 are 1 mol / L and 2 mol / L respectively; KOH is added to deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of LiF and AlCl3 is added to an equal volume of a mixed solution of KOH and LiCl, and the mixture is reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain an in-situ fluorinated lithium aluminum layered double hydroxide.
[0085] Fig.11 and Fig.12 The SEM and XRD test results of the product obtained in Example 5 are shown respectively. It can be seen that similar to Example 2, when the input amounts of other elements are consistent with the theoretical stoichiometric ratio of the product composition, only OH - When the source is in excess of 50%, pure LiAl-Cl, F LDH can be obtained. The product shows the morphology characteristics of the closely stacked growth of the lamellar structure.
[0086] Comparative Example 1
[0087] LiF and Al(OH)3 are dispersed in deionized water and mixed to form a dispersion, wherein the concentrations of LiF and Al(OH)3 are 1 mol / L and 2 mol / L, respectively; KOH powder is added to deionized water to dissolve and form a 9 mol / L KOH solution; the mixed solution of LiF and Al(OH)3 is added to an equal volume of KOH solution, and the mixture is reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain a final product.
[0088] In Comparative Example 1, Al 3+ The source is changed to insoluble Al(OH)3, so LiF cannot dissolve to form a solution, and the resulting product is in the form of coarse blocks ( Fig.13 ). It can be seen that under the same reaction conditions, Fig.14XRD analysis shows that the product still contains a relatively high intensity LiF impurity peak, but no Al(OH)3 diffraction peak exists.
[0089] Comparative Example 2
[0090] LiF and AlPO4 are dispersed in deionized water and mixed to form a dispersion, wherein the concentrations of LiF and Al(OH)3 are 1 mol / L and 2 mol / L, respectively; KOH powder is added to deionized water to dissolve and form a 9 mol / L KOH solution; the mixed dispersion of LiF and AlPO4 is added to an equal volume of KOH solution, and reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and dried in an oven at 80°C to obtain a final product.
[0091] In Comparative Example 2, Al 3+ The source was changed to slightly soluble AlPO4, and XRD analysis showed that the product still contained a large amount of AlPO4 impurities ( Fig.16 ), indicating that under the same reaction conditions, only part of the reactants participated in the reaction. The SEM image shows that the obtained product has a flower cluster-like lamellae stacking morphology ( Fig.15 ).
[0092] Comparative Example 3
[0093] Al(NO3)3·9H2O was dispersed in deionized water and dissolved to form a 2 mol / L Al(NO3)3 solution. KOH and LiF powders were added to deionized water and dissolved to form a 6 mol / L KOH and 1 mol / L LiF mixture. The Al(NO3)3 solution was added to an equal volume of the KOH and LiF mixture, and the mixture was reacted at 90°C and 500 rpm for 6 h at normal pressure to form a suspension. The suspension was filtered and washed, and the white filter cake was collected and dried in an oven at 80°C to obtain the final product.
[0094] Compared with Example 1, in Comparative Example 3, only the addition method of LiF was changed, so LiF could not be dissolved to form a solution. Fig.17 It can be seen that the product is a morphology in which a large number of nanoparticles and nanosheets coexist. Fig.18 It can be seen from the XRD pattern that the product prepared in Comparative Example 3 contains both high-intensity and sharp LiAl LDH phase diffraction peaks and Al(OH)3 impurity peaks, indicating that a large amount of Al(OH)3 impurities exist as the main product, while the product prepared in Example 1 contains only a trace amount of Al(OH)3 impurities; it shows that under the same reaction conditions, the Li + The reaction kinetics of insertion into the Al(OH)3 structure are insufficient.
[0095] Comparative Example 4
[0096] LiNO3 and Al(NO3)3·9H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiNO3 and Al(NO3)3 are 1 mol / L and 2 mol / L respectively; KOH powder is added to deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of LiNO3 and Al(NO3)3 is added to an equal volume of KOH solution, and reacted at 90°C and 500 rpm for 6 hours under normal pressure to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and placed in an oven at 80°C for drying to obtain lithium aluminum double metal hydroxide;
[0097] KF is dispersed in deionized water so that the molar ratio of KF to LiNO3 added in the above step is 1:1, and dissolved to form a 1 mol / L KF solution; all the lithium aluminum double hydroxide powder products obtained in the above step are dispersed in the KF solution, and reacted at 90°C under normal pressure for 6 hours; the suspension is washed and filtered, and the white filter cake is collected and placed in an oven at 80°C for drying to obtain a fluorinated lithium aluminum layered double hydroxide.
[0098] Comparative Example 5
[0099] Li2SO4 and Al2(SO4)3·18H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of Li2SO4 and Al2(SO4)3 are 0.5 mol / L and 1 mol / L, respectively; KOH powder is added into deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of Li2SO4 and Al2(SO4)3 is added into an equal volume of KOH solution, and reacted at 90°C and 500 rpm under normal pressure for 6 hours to form a suspension; the suspension is filtered and washed, and the white filter cake is collected and dried in an oven at 80°C to obtain lithium aluminum double hydroxide.
[0100] KF is dispersed in deionized water so that the molar ratio of KF to Li2SO4 added in the above step is 1:0.5, and dissolved to form a 1 mol / L KF solution; all the lithium aluminum double hydroxide powder products obtained in the above step are dispersed in the KF solution, and reacted at 90°C under normal pressure for 6 hours; the suspension is washed and filtered, and the white filter cake is collected and placed in an oven at 80°C for drying to obtain a fluorinated lithium aluminum layered double hydroxide.
[0101] Comparative Example 6
[0102] LiCl and AlCl3·6H2O are dispersed in deionized water and dissolved to form a mixed solution, wherein the concentrations of LiCl and AlCl3 are 1 mol / L and 2 mol / L respectively; KOH powder is added into deionized water and dissolved to form a 9 mol / L KOH solution; the mixed solution of LiCl and AlCl3 is added into an equal volume of KOH solution, and reacted at 90°C and 500 rpm for 6 hours under normal pressure to form a suspension; the suspension is filtered and washed, and a white filter cake is collected and placed in an oven at 80°C to be dried to obtain lithium aluminum double hydroxide.
[0103] KF is dispersed in deionized water so that the molar ratio of KF to LiCl added in the above step is 1:1, and dissolved to form a 1 mol / L KF solution; all the lithium aluminum double hydroxide powder products obtained in the above step are dispersed in the KF solution, and reacted at 90° C. under normal pressure for 6 hours; the suspension is washed and filtered, and the white filter cake is collected and placed in an oven at 80° C. to obtain a fluorinated lithium aluminum layered double hydroxide.
[0104] Effect Example
[0105] (1) XRD and SEM testing
[0106] 1. X-ray diffraction (XRD) test: An X-ray diffractometer (model: D2 PHASER) from Bruker AXS was used for phase analysis.
[0107] 2. Scanning electron microscope (SEM) test: A scanning electron microscope (model: SIGMA 300) from Zeiss (ZEISS) was used for morphology analysis.
[0108] (2) Thermal shrinkage test
[0109] In parts by mass, 25 parts of the in-situ fluorinated lithium aluminum layered double hydroxide prepared in Example 2, 0.25 parts of sodium hexametaphosphate, 1.5 parts of 16% mass fraction of polyvinyl alcohol (average molecular weight of 146000-186000, 99% hydrolyzed) and 0.6 parts of 20% mass fraction of polyacrylic acid (average molecular weight of 100000) are mixed in 80 parts of deionized water and stirred evenly to prepare a coating layer slurry, the coating slurry is placed in a vacuum dryer for defoaming treatment, and then the slurry is evenly coated on one side surface of the porous PE base film by micro-gravure roller coating, and after drying and winding, a coated modified secondary battery separator is obtained.
[0110] Thermal shrinkage rate measurement: According to the provisions of GB / T 363-2018, a 10 cm × 10 cm diaphragm was cut from the film roll, with the length and width of the diaphragm in the longitudinal direction (MD) and transverse direction (TD) of the diaphragm, respectively. The diaphragm was placed in an electric constant temperature blast drying oven (model: DGG-9036A) of Shanghai Qixin at a set temperature of 180°C for 1 hour for measurement. The thermal shrinkage rate in different directions is calculated by formula 1:
[0111] Formula 1: Thermal shrinkage rate (%) = ((length before heating - length after heating) / length before heating) × 100.
[0112] The prepared coated modified secondary battery separator has an average thermal shrinkage of no more than 2.0% at 180° C., and the PE base film under the same conditions is completely melted and breaks.
[0113] (3) Element content test
[0114] X-ray photoelectron spectroscopy (EDS) test: The F and O element contents were analyzed using a SEM-based X-ray photoelectron spectrometer (model: XFlash Detector 630M) from Bruker NanoAnalysis Division (Bruker BNA). The test results are shown in Table 1.
[0115] Plasma Inductively Coupled Plasma Emission Spectrometer (ICP) Test: The Li and Al element contents were analyzed using an inductively coupled plasma emission spectrometer (model: Avio 200) from PerkinElmer. The test results are shown in Table 1.
[0116] Table 1
[0117]
[0118] The chemical formula of lithium aluminum layered double hydroxide is [LiAl2(OH)6] + (A n– 1 / n )·mH2O, it can be seen that the theoretical molar ratio of Li:Al is 1:2. As can be seen from Table 1, except for Example 1, the ICP analysis results of Examples 2-6 and Comparative Examples 4-6 show that the molar ratio of Li:Al is close to 1:2, indicating that the LiAl LDH in the product has an ideal elemental composition and phase purity, which is consistent with the XRD test results of the corresponding examples. The EDS test results of the products prepared by each embodiment and comparative example in Table 1 all show the presence of F, indicating the realization of F intercalation doping. The F content in Example 3 is as high as 8.4wt.%, taking into account that LiAlLDH aqueous solution mostly exists as a dihydrate, when the interlayer is completely F -During intercalation, the chemical formula of the fluorinated lithium aluminum layered double hydroxide can be expressed as [LiAl2(OH)6]F·2H2O, wherein the theoretical mass content of F atoms is 8.7wt.%, which indicates that Example 3 can achieve nearly complete interlayer intercalation fluorination. In contrast, the F element content of Comparative Examples 4-6 is relatively low, and the preparation method of Comparative Examples 4-6 requires an additional fluorination step, which is not only cumbersome but also increases production costs. At the same time, the fluorine source of KF in Comparative Examples 4-6 only serves to provide F, while LiF in Examples 1-6 serves as a reactant, and both Li and F participate in the formation of the product, and LiAl LDH and F intercalation are synthesized at the same time, which does not cause a waste of Li source. The in-situ fluorine intercalation method for preparing lithium aluminum layered double hydroxide of the present invention is very simple in the structure formation process of LiAl LDH. - Intercalation is achieved by entering the interlayers, and the reactants all have a high concentration. The preparation method is simple and efficient, easy to operate, low cost and avoids the waste of water resources to a large extent.
[0119] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing an in-situ fluorinated lithium aluminum layered double hydroxide, characterized in that: The steps include: The "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is mixed with an alkaline reagent to form a suspension through reaction, and then solid-liquid separation is performed to obtain the in-situ fluorinated lithium aluminum layered double metal hydroxide; The molar ratio of the lithium fluoride to the aluminum element in the strong acid salt of aluminum is 1:2; the OH provided by the alkaline reagent in the reaction system - The molar ratio of the aluminum element to the aluminum strong acid salt is not less than 3:
1.
2. The method for preparing the in-situ fluorinated lithium aluminum layered double hydroxide according to claim 1, characterized in that: The strong acid salt of aluminum is one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; And / or, the solvent in the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" is deionized water and / or an alcohol solvent; And / or, in the "mixed solution containing lithium fluoride and a strong acid salt of aluminum", the concentration of the strong acid salt of aluminum does not exceed the concentration corresponding to its maximum solubility at the temperature of the solvent, preferably 0.5-6 mol / L.
3. The method for preparing the in-situ fluorinated lithium aluminum layered double metal hydroxide according to claim 1, characterized in that: The alkaline reagent is capable of providing OH by ionization and / or hydrolysis in the reaction system. - The substance is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia monohydrate, sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate, and more preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide and ammonia monohydrate; And / or, the OH provided by the alkaline reagent in the reaction system - The molar ratio of the aluminum element to the strong acid salt of aluminum is greater than 3:1, preferably (3-18):1 but not including 3:1, and more preferably (3-12):1 but not including 3:
1.
4. The method for preparing the in-situ fluorinated lithium aluminum layered double hydroxide according to claim 1, characterized in that: The alkaline reagent is mixed with the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" in the form of an alkaline reagent solution; The concentration of the alkaline reagent solution is preferably not more than the concentration corresponding to its maximum solubility at the temperature in the solvent, and is more preferably 0.5-10 mol / L; the solvent in the alkaline reagent solution is preferably deionized water and / or an alcohol solvent; preferably, the "mixed solution containing a strong acid salt of lithium fluoride and aluminum" is added to the alkaline reagent.
5. The method for preparing the in-situ fluorinated lithium aluminum layered double hydroxide according to claim 1, characterized in that: A non-lithium fluoride lithium salt is also added prior to the reaction.
6. The method for preparing the in-situ fluorinated lithium aluminum layered double hydroxide according to claim 5, characterized in that: The non-lithium fluoride lithium salt is a lithium salt that can be completely dissolved in the reaction system after the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" and the alkaline reagent are mixed; The non-fluoride lithium salt is preferably one or more of lithium nitrate, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium acetate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium sulfonate; And / or, the molar ratio of lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is (0.1-2):1, preferably (0.1-1):1; And / or, the non-lithium fluoride lithium salt is added to the "mixed solution containing lithium fluoride and a strong acid salt of aluminum", or first mixed with the alkaline reagent, or added to the reaction system after the "mixed solution containing lithium fluoride and a strong acid salt of aluminum" and the alkaline reagent are mixed.
7. The method for preparing an in-situ fluorinated lithium aluminum layered double hydroxide according to claim 5, characterized in that: When the OH provided by the alkaline reagent in the reaction system - When the molar ratio of the aluminum element in the strong acid salt of aluminum is 3:1, the molar ratio of the lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is (0.1-2):1; Or, when the OH provided by the alkaline reagent in the reaction system - When the molar ratio of the aluminum element in the strong acid salt of aluminum is greater than 3:1, the molar ratio of the lithium ions in the non-lithium fluoride lithium salt to the lithium fluoride is (0.1-2):
1.
8. The method for preparing an in-situ fluorinated lithium aluminum layered double hydroxide according to claim 1, characterized in that: The reaction temperature is 5-200°C, preferably 10-100°C, more preferably 25-95°C; And / or, the reaction time is 0.5-96h, preferably 3-72h, more preferably 3-48h.
9. An in-situ fluorinated lithium aluminum layered double metal hydroxide prepared by the method for preparing an in-situ fluorinated lithium aluminum layered double metal hydroxide according to any one of claims 1 to 8.
10. Use of the in-situ fluorinated lithium aluminum layered double metal hydroxide as claimed in claim 9 in a lithium secondary battery separator coating.
Citation Information
Patent Citations
Preparation method of nitrate radical intercalation lithium-aluminum layered bimetal hydroxide
CN107500321A